STRATEGI POLITIK PEREMPUAN DALAM DOMINASI SISTEM PATRIARKI BATAK TOBA - Diana Anastasia Hutabarat; Warsito . (Journal of Politic and Government Studies, 2019)
After the passage of the law on women's representation in political parties caused women to enter politics. This makes political parties with the incessant recruitment of women to fulfill the Legislative Election Law which requires 30% representation of women in the General Election process. So that the results of the Pematangsiantar City Legislative Election in 2014 achieved success and improvement in the Candidates applying for the 2009 Legislative Election and Female Candidates who won Pileg as many as 7 people while the 2019 Pileg as many as 3 of the Many Candidates applying to make candidates who succeeded in holding positions became a member of the Pematangsiantar City DPRD for the period 2014-2019. However, the issue in the midst of the Batak Toba patriarchal system that impedes the process of selecting women to enter the world of politics is still an obstacle for women to be reluctant to enter politics, so that people always perceive that politics is a world of men and women should be in the region domestic so that women are always seen as the second person after men, The discussion of this study explains (1) women's political strategy by female candidates in winning the 2014 legislative election pematangsiantar city, (2) to explain things that are a barrier to women in the domination of the Toba Batak Patriarchy. (3) To find out the views of the Batak Toba patriarchal community regarding the representation of women in legislative elections and the influence of the domination of the Batak Toba patriarchy itself.Keywords: Strategy, Politics, Women, and the Patriarchal System.